Commentary on Zhou and Fabian (2021) - Farbood, Morwaread M. (Empirical Musicology Review, 2023)
This is a commentary on Zhou and Fabian's article, "Velocity and Virtuosity: An Empirical Investigation of Basic Tempo in Contemporary Performances of Two Large-scale Works of Chopin and Liszt".